2007
DOI: 10.1007/s10640-007-9171-y
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Changes in the Quality of Coral Reef Ecosystems: A Stated Preference Study of SCUBA Diving in the Bonaire National Marine Park

Abstract: Coral reef, Marine protected area, Non-market valuation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 15 publications
(10 reference statements)
3
50
0
2
Order By: Relevance
“…Second, reduced catch of juveniles could result in a greater number of reproductively mature fish, thereby increasing population productivity. Third, reduced catch of bycatch fish could increase biodiversity, and thereby tourist interest, since many recreational divers consider species diversity a key attraction of coral reef dives (Parsons & Thur 2008). Escape gaps have great potential to benefit both fishermen and conservation, and requiring escape gaps in all reef environments where traps are used would represent an important step towards sustainable management.…”
Section: Discussionmentioning
confidence: 99%
“…Second, reduced catch of juveniles could result in a greater number of reproductively mature fish, thereby increasing population productivity. Third, reduced catch of bycatch fish could increase biodiversity, and thereby tourist interest, since many recreational divers consider species diversity a key attraction of coral reef dives (Parsons & Thur 2008). Escape gaps have great potential to benefit both fishermen and conservation, and requiring escape gaps in all reef environments where traps are used would represent an important step towards sustainable management.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that the value of Bonaire's reefs could decrease by up to US$538 million year -1 if underwater visibility, coral cover and species diversity declined below certain thresholds (Parsons and Thur 2008). Although reef degradation has already occurred in Bonaire (Bak and Nieuwland 1995;Bak et al 2005 Finally, the apparent decline in acceptance of diver user fees (97% for the US$10 fee in 2002 (Uyarra 2002) vs. 90% for the $25 fee in this study) may be because acceptance of higher fees may increase gradually over time, or the new fee may be close to the maximum WTP.…”
Section: Changing Attitudes Toward Bnmp User Feesmentioning
confidence: 99%
“…Divers may also be less willing to pay a conservation access fee as the quality of a dive site declines in terms of visibility, species diversity, and coral cover (Parsons and Thur 2008). The continued growth of recreational diving is thus a threat to both the ecological and economic sustainability of reefs (Davis and Tisdell 1995) and should be considered in the planning of effective marine resource management strategies.…”
mentioning
confidence: 99%